Students English Speaking Ability by Using Bamboo Dancing Learning Model - Weke, Laurensius (BAHTRA: Pendidikan Bahasa dan Sastra, 2021)
Student learning outcomes at UPTD SMP Negeri 1 Lobalain have not reached the minimum passing criteria in English language learning due to inappropriate choice of learning models so that students are less motivated to learn. For this reason, this research was conducted to improve English speaking skills by applying the Bamboo Dancing learning model in class IX UPTD SMP Negeri 1 Lobalain. The results showed that (1) Teacher activity in cycle 1 was 76%, and increased in cycle 2 which was 83%. (2) student activity in cycle 1 was 68%, in cycle 2 it increased to 78% (3) student learning completeness in cycle 1 was 67.7%, and increased in cycle 2 by 87.1%. Based on the results of data analysis, it can be concluded that the application of the Bamboo Dancing Learning Model is very suitable for use in English language learning and can improve the learning outcomes of students in class IX UPTD SMP Negeri 1 Lobalain